2021
DOI: 10.1183/16000617.0078-2021
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic involvement and imaging patterns in IgG4-related disease

Abstract: ObjectiveImmunoglobulin G4-related disease (IgG4-RD) is a rare orphan disease. Lung, pleura, pericardium, mediastinum, aorta and lymph node involvement has been reported with variable frequency and mostly in Asian studies. The objective of this study was to describe thoracic involvement assessed by high-resolution thoracic computed tomography (CT) in Caucasian patients with IgG4-RD.MethodsThoracic CT scans before treatment were retrospectively collected through the French case registry of IgG4-RD and a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Because the patient was asymptomatic and the disease was stable, no specific treatment was indicated. We plan to monitor the patient and conduct periodic physical examinations, laboratory testing, and surveillance CT. As IgG4‐RLD can present with various types of radiological findings, 1 IgG4‐RLD is often misdiagnosed as lung cancer. IgG4‐RLD generally manifests as mild clinical symptoms, despite the degree of lesions and their spread, determined in the imaging analysis, and excessive cellular infiltration, observed during pathological examinations 2 .…”
Section: Clinical Imagementioning
confidence: 99%
“…Because the patient was asymptomatic and the disease was stable, no specific treatment was indicated. We plan to monitor the patient and conduct periodic physical examinations, laboratory testing, and surveillance CT. As IgG4‐RLD can present with various types of radiological findings, 1 IgG4‐RLD is often misdiagnosed as lung cancer. IgG4‐RLD generally manifests as mild clinical symptoms, despite the degree of lesions and their spread, determined in the imaging analysis, and excessive cellular infiltration, observed during pathological examinations 2 .…”
Section: Clinical Imagementioning
confidence: 99%
“…Despite solid lung nodules being reported in 33% of patients with IgG4‐RLD, the frequency of a mass lesion occurrence is not accurately known. 2 Respirologists should be some IgG4‐RLD may not need steroid therapy.…”
Section: Clinical Imagementioning
confidence: 99%
“…Observational studies have shown that radiological presentation of pulmonary involvement in IgG4‐RD is polymorphic and often non‐specific. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary involvement is relatively less frequent but is probably underestimated. Observational studies have shown that radiological presentation of pulmonary involvement in IgG4‐RD is polymorphic and often non‐specific 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation